2006
DOI: 10.1111/j.1440-1827.2006.02010.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of RUNX3 methylation in neoplastic and non‐neoplastic gastric epithelia using a DNA microarray

Abstract: Silencing of the RUNX3 gene by hypermethylation of its promoter CpG island plays a major role in gastric carcinogenesis. To quantitatively evaluate RUNX3 methylation, a fiber-type DNA microarray was used on which methylated and unmethylated sequence probes were mounted. After bisulfite modification, a part of the RUNX3 promoter CpG island, at which methylation is critical for gene silencing, was amplified by polymerase chain reaction using a Cy5 end-labeled primer. Methylation rates (MR) were calculated as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 13 publications
0
12
0
1
Order By: Relevance
“…In agreement, recent work found that P2 methylation levels of <10% can be reported as ‘hypermethylated’ by MSP. 45 …”
Section: Discussionmentioning
confidence: 99%
“…In agreement, recent work found that P2 methylation levels of <10% can be reported as ‘hypermethylated’ by MSP. 45 …”
Section: Discussionmentioning
confidence: 99%
“…showed that RUNX3 expression was decreased in 60% of primary human gastric tumors; with nearly 90% of late stage tumors that represent highly metastatic tumors showing reduced RUNX3 levels. An analysis of clinical tissue samples from peritoneal metastases arising from gastric cancers showed that RUNX3 expression decreased significantly in the metastatic tissue, compared to normal gastric mucosa or primary main tumors 19, 20. Therefore, RUNX3 deficiency is closely associated with gastric cancer metastasis.…”
mentioning
confidence: 99%
“…The successful identification of differentially methylated regions (DMRs) associated with aging in studies of candidate loci (12)(13)(14) has stimulated interest in mapping all such sites * To whom correspondence should be addressed at: Center for Biomarker Research and Personalized Medicine, McGuire Hall, Medical College of Virginia campus, Virginia Commonwealth University, 1112 East Clay Street, Richmond, VA 23298, USA. Tel: +1 8048283428; Fax: +1 8046283991; Email: jlmcclay@vcu.edu genome-wide.…”
Section: Introductionmentioning
confidence: 99%